S7 Does completion of a pulmonary rehabilitation programme improve patient activation scores?. (12th November 2019) - Barber, DS; Pilsworth, S; Frost, F; Wat, D; Sibley, S
Abstract : Introduction: Patient Activation Measure (PAM) is a validated patient reported-measure that measures patients' knowledge, skill, and confidence to manage their own health and care (Hibbard J.H. et al . Health Serv Res. 2005 Dec; 40:1918–30). Patients with low activation scores are often frequent users of elective & emergency medical services. Aim: To explore changes in activation via PAM scores for patients who completed a course of Pulmonary Rehabilitation (PR) against those who failed to complete. Methods: 201 patients from the Knowsley Community Respiratory Service participated in PR between April 2016 and December 2018 and completed PAM questionnaires before and after the programme. Results: There were 103 males (76 completed), 98 females (78 completed) with a median age of 69 (44– 93), median FEV1% predicted of 65 (22– 117), median BMI of 28 (17– 47) and 52 were smokers (25% of completers versus 28% of non-completers). 154 patients completed the program with a median (95% CI) PAM change of +5.53 (3.5 to 7.5), versus 47 who did not complete with a change in PAM of -2.1 (-5.7 to 2.1) points, difference between the groups 6.7 (2.5 to 10.7) p<0.001. Median baseline PAM scores were identical between the groups (51.0 vs 51.0) p=0.76. Additionally, a higher proportion of PR completers improved by at least 1 PAM level, 67/154 (43.5%) versus 11/47 (23.4%) non-completers X 2 p=0.01. Conclusion: Successful completion of a course of PR is associated with a significant positive improvement in PAM score. Baseline PAM doesn't appear to be an indicator of future completion of PR. This reaffirms that PR plays a role in improving self-management in COPD and completion of the programme should be highly encouraged.